2019
DOI: 10.9734/sajrm/2019/v3i230081
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Screening for Antibacterial Properties of the Male Flowers of Phoenix dactylifera

Abstract: Objective: The aim of this study was to evaluate the antibacterial potential of the male flowers of Phoenix dactylifera (date palm tree) against five Gram-positive and five Gram-negative bacteria. Methods: Male flowers were collected and extracted by maceration using 80% methanol and the antibacterial activity was determined using cup-plate diffusion test, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests. Results: The methanol extract of male flowers of Phoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Regarding fatty acids, a study carried out in Egypt on DPP from the El-Hayani variety identified 13 fatty acids, with palmitic acid (34.45%) and linoleic acid (14.24%) having the highest concentrations [ 10 ]. Additionally, oleic, linolenic, stearic, margaric, behenic, arachidonic, and lignoceric acids were also detected at high levels in Egyptian and Moroccan DPP [ 9 , 11 , 77 ]. Furthermore, palmitic, oleic, and linoleic acids were the major fatty acids identified in the Khikri and Samsami varieties of Iraqi DPP [ 39 ].…”
Section: Exploring Mechanisms: How Date Palm Pollen Composition Influ...mentioning
confidence: 99%
“…Regarding fatty acids, a study carried out in Egypt on DPP from the El-Hayani variety identified 13 fatty acids, with palmitic acid (34.45%) and linoleic acid (14.24%) having the highest concentrations [ 10 ]. Additionally, oleic, linolenic, stearic, margaric, behenic, arachidonic, and lignoceric acids were also detected at high levels in Egyptian and Moroccan DPP [ 9 , 11 , 77 ]. Furthermore, palmitic, oleic, and linoleic acids were the major fatty acids identified in the Khikri and Samsami varieties of Iraqi DPP [ 39 ].…”
Section: Exploring Mechanisms: How Date Palm Pollen Composition Influ...mentioning
confidence: 99%